2017
DOI: 10.1194/jlr.m075044
|View full text |Cite
|
Sign up to set email alerts
|

GPR120 suppresses adipose tissue lipolysis and synergizes with GPR40 in antidiabetic efficacy

Abstract: GPR40 and GPR120 are fatty acid sensors that play important roles in glucose and energy homeostasis. GPR40 potentiates glucose-dependent insulin secretion and demonstrated in clinical studies robust glucose lowering in type 2 diabetes. GPR120 improves insulin sensitivity in rodents, albeit its mechanism of action is not fully understood. Here, we postulated that the antidiabetic efficacy of GPR40 could be enhanced by coactivating GPR120. A combination of GPR40 and GPR120 agonists in / mice, as well as a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 41 publications
4
24
0
1
Order By: Relevance
“…FA binding to GPR40 on pancreatic β-cells leads to activation of several signaling pathways involved in insulin secretion and targeting this receptor has shown to be a promising new treatment for T2DM, however safety concerns (hepatotoxicity) associated with current lead compounds have precluded their clinical use 6 . Recently, a dual GPR40 and GPR120 agonist showed potent activity on both adipose tissue lipolysis and glucose metabolism, highlighting the strong potential of these receptors in FA and glucose metabolism 7 .…”
mentioning
confidence: 99%
“…FA binding to GPR40 on pancreatic β-cells leads to activation of several signaling pathways involved in insulin secretion and targeting this receptor has shown to be a promising new treatment for T2DM, however safety concerns (hepatotoxicity) associated with current lead compounds have precluded their clinical use 6 . Recently, a dual GPR40 and GPR120 agonist showed potent activity on both adipose tissue lipolysis and glucose metabolism, highlighting the strong potential of these receptors in FA and glucose metabolism 7 .…”
mentioning
confidence: 99%
“…Activation of GPR120 induces release of Fgf21 in BAT 35 . Interestingly, it has been shown that GPR120 suppresses adipose tissue lipolysis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been put into the generation of FFA4 receptor agonists, however, it appears that none have yet reached clinical testing. An interesting concept has been advanced from demonstrations that simultaneous activation of FFA1 and FFA4 receptors has synergistic anti‐diabetic effects in animal models by virtue of dual glucose‐lowering and insulin‐sensitizing effects (Oh et al ., ; Satapati et al ., ). It has been proposed that a dual FFA1/FFA4 receptor agonist could be a highly efficacious anti‐diabetic agent as it is acting on several key tissues (i.e.…”
Section: Exploring Gpcr‐based Mechanisms To Increase Circulating Glp‐1mentioning
confidence: 97%